A Review on Trade Secrets (International Journal of Food and Nutritional Sciences, 2022)
Trade secrets are intangible assets for a business that have the ability to provide it a competitive advantage over its rivals. Companies have been forced to preserve such trade secrets inside the confines of the company due to increased market rivalry. The Indian government, on the other hand, has fallen behind in providing sufficient protection for trade secrets. While trade secrets are often overlooked in favor of more visible elements of intellectual property rights, it is critical for businesses to protect their private data and procedures. In India, trade secrets are enforced either contractually or via a rudimentary application of common law principles. This study aims to investigate India's trade secret protection system and the serious consequences of insufficient trade secret protection on market conditions. The authors of this article attempt to demonstrate the necessity for a distinct piece of law governing trade secrets. The method used is based on secondary research, which includes a study of the legislation in different countries across the globe. In order to promote the development of a globalized economy, the study suggests that, given the potential that trade secrets have for a company, appropriate protection must be formulated under the Indian IPR system. The purpose of this article is to add to the current literature on trade secrets and their protection in India, as well as to examine the unique arrangements established in other nations.